دور التمكين في تحقيق الرضا الوظيفي لدى العاملين - منال, سعداوي; أمينة, فتح الله; شهرزاد, سيار (University of eloued جامعة الوادي, 2020)
" تناولت هذه الدراسة موضوع دور التمكين في تحقيق الرضا الوظيفي لدى العاملين ، ولقد تم اختبار هذه الدراسة في قطاع البنوك بمدينة الوادي ممثلا ببنوك عامة وأخرى خاصة. وطبقت الدراسة على عينة من الموظفين مكونة من 30 موظف بالنسبة للبنوك العامة، و 30 موظف بالنسبة للبنوك الخاصة، حيث استخدمت الدراسة الاستبيان كأداة رئيسية لجمع البيانات فضلا عن المقابلات الشخصية، والملاحظة الميدانية والوثائق. وتم توزيع الاستبيان عشوائيا على مختلف الموظفين في البنوك المبحوثة، وذلك على اختلاف مستوياتهم الوظيفية، وخلصت الدراسة إلى مجموعة من النتائج من أهمها ما يلي:  مستوى إدراك التمكين والرضا الوظيفي لدى العاملين بالبنوك الخاصة والعامة متوسط.  توجد علاقة ارتباط موجبة ذات دلالة إحصائية عند مستوى معنوية (α≤0.05) ، بين التمكين والرضا الوظيفي لدى العاملين في عينة البنوك المبحوثة بمدينة الوادي.  تبين من خلال نتائج الانحدار الخطي المتعدد أنهلا توجدعلاقة تأثير بين الابعاد (بعد التدريب وبعد امتلاك المعرفة وبعد الاستقلالية في اتخاذ القرار) والرضا الوظيفي لدى العاملين  توجد علاقة تأثير ذات دلالة إحصائية بعد التدريب وبعد التحفيز على ابتكار العاملين ببنك الخليج بمدينة االوادي  تبين من خلال نتائج الانحدار الخطي المتعدد أنه توجد علاقة ارتباط موجبة ذات دلالة إحصائية عند مستوى معنوية (α≤0.05)فإنه هناك علاقة تأثير بين الابعاد ( بعد تفويض السلطة والتحفيز وفرق العمل) وبين الرضا الوظيفي لدى العاملين أما فيما يخص الفروق في ابعاد التمكين والرضا الوظيفي فلا توجد فروق ذات دلالة احصائية في مستوى معنوية (α≤0.05 بين البنوك العامة والخاصة. "" This study deals with the issue of the role of empowerment in achieving job satisfaction for employees ,this study has been tested in the baking sector in the valley, represented by public and private banks. The study was applied to a sample of 30 employees for public banks and 30 employees for private banks. The study used The questionnaire as a main tool for data collection as well as personal interviews, fieldnotes and documents ,The questionnaire was distributed randomly to various employees in The researched banks, regardlessof their job level, and the study concluded with a set of results , The most important of which are following: The level of empowerment perception and job satifaction among employees of private and public banks is average There is a positive correlation with statistically significant at a between empowerment and job (α≤0.05)significant level Satisfaction among workers in The sample of banks searched in The valley It was found though the results of linear regression that it is polymorphic between dimension: after training, after acquiring knowledge, and after independence in decision-making, and amployee job satisfaction. There is a statistically significant effect relationship after training and after stimulation on job satisfaction. It was found through the results of multiple linear regression that there is a positive correlation relationship with statistical , so there is an (α≤0.05) significance at a significant level Influentail relationship between the dimensions: after delegating authority, motivation and work teams and between employee job satisfaction. As for the differences in the dimensions of empowerment and job satifaction, there are no statisfaction, there are no statistically significant differences in the level of Between public and private banks.(α≤0.05) significqnce "
مذكرة ماستر ادارة اعمال
Keywords: مكين العاملين، الرضا الوظيفي، بنوك خاصة، بنوك عامة ، مدينة الوادي.; Empowement of workers, job satiction, private banks, public banks, public banks, eloued